EKSPRESI ANTI-HELICOBACTER PYLORI PADA GASTRITIS KRONIS, LESI PRAKANKER, DAN KARSINOMA GASTER - Lina Damayanti; Bambang Hendro Putranto; Udadi Sadhana (Universitas Muhamadiyah Surakarta, 2015)
Prevalence of Helicobacter pylori infection in Indonesia was 36-46%. In Jakarta and Surabaya, the prevalence were 85,7%-93,9%. Helicobacter pylori infection play role in pathogenesis of pectic ulcers, chronic gastritis, carcinoma of gaster and gastric lymphoma. Epidemiologic study showed 80% of carcinoma of gaster related with H pylori infection.This study analyzed expression of anti-Helicobacter pylori in chronic gastritis, precancer lesion , and carcinoma of gaster. This study was a observational descriptive study with case control design. Thirty (30) samples from paraffin bloc that were diagnosed with chronic gastritis, precancer lesion, and carcinoma of gaster at Dokter Kariadi hospital in 2013 was stained by hematoxylin eosin, giemsa and immunohistochemistry of anti-helicobacter pylori. Data was analyzed by descriptive analysis. Thirty (30) samples were diagnosed as gastritis chronis 13 (43,3% ), pra cancer lesion(36.6%), and carcinoma(20.1%). Chronic gastritis can be occurred at all age and no distinct difference on sex, while gastric carcinoma predominant in male older than 40 years. Expresion of Helicobacter pylori on chronic gastritis was 84.6%, precancer lesion was 54.5%, and gastric carcinoma was 83.3%. The Giemsa stain gave 23.3% false positive and 20% false negative. Helicobacter pylori expression can be showed in chronic gastritis, precancer lesion, and gastric carcinoma.Keywords: Chronic gastritis, gastric carcinoma, Helicobacter pylori